IFT81, encoding an IFT-B core protein, as a very rare cause of a ciliopathy phenotype. Issue 10 (14th August 2015) - Perrault, Isabelle; Halbritter, Jan; Porath, Jonathan D; Gérard, Xavier; Braun, Daniela A; Gee, Heon Yung; Fathy, Hanan M; Saunier, Sophie; Cormier-Daire, Valérie; Thomas, Sophie; Attié-Bitach, Tania; Boddaert, Nathalie; et al.
Abstract : Background: Bidirectional intraflagellar transport (IFT) consists of two major protein complexes, IFT-A and IFT-B. In contrast to the IFT-B complex, all components of IFT-A have recently been linked to human ciliopathies when defective. We therefore hypothesised that mutations in additional IFT-B encoding genes can be found in patients with multisystemic ciliopathies. Methods: We screened 1628 individuals with reno-ocular ciliopathies by targeted next-generation sequencing of ciliary candidate genes, including all IFT-B encoding genes. Results: Consequently, we identified a homozygous mutation in IFT81 affecting an obligatory donor splice site in an individual with nephronophthisis and polydactyly. Further, we detected a loss-of-stop mutation with extension of the deduced protein by 10 amino acids in an individual with neuronal ceroid lipofuscinosis-1. This proband presented with retinal dystrophy and brain lesions including cerebellar atrophy, a phenotype to which the IFT81 variant might contribute. Cultured fibroblasts of this latter affected individual showed a significant decrease in ciliated cell abundance compared with controls and increased expression of the transcription factor GLI2 suggesting deranged sonic hedgehog signalling. Conclusions: This work describes identification of mutations of IFT81 in individuals with symptoms consistent with the clinical spectrum of ciliopathies. It might represent the rare case of a core IFT-B complex protein found associated with human disease. Our data further suggest that defects in the IFT-B core are an exceedingly rare finding, probably due to its indispensable role for ciliary assembly in development.